"I thought I was supposed to get an A in PE!" Successes and challenges of teachers and administrators implementing standards-based grading in physical education. (September 2021) - Townsley, Matt; McNamara, Scott
Highlights: Educators perceived the implementation of SBG in PE was often nebulous. Teachers appeared to have a surface-level understanding of the state PE standards. SBG enhances physical educators' teaching and assessment practices. Abstract: The purpose of this research was to understand the initial successes and challenges of physical educators' implementation of standards-based grading (SBG) practices. Using a qualitative descriptive approach, the researchers interviewed four physical educators and two school administrators from a rural K-12 school in the Midwest. Although participants expressed a "building the plane as we fly it" mindset towards the training and implementation so far, benefits included a better roadmap to improving instruction and assessment to enhance student motivation. The participants in this study did not report much formal SBG training, yet their efforts to implement these practices created a PE environment in which some students were motivated to participate and extend their learning at home.